Epidemiological Pattern of Hepatitis B and Hepatitis C as Etiological Agents for Hepatocellular Carcinoma in Iran and Worldwide - Zidan, Ahmed (Kowsar, 2012)
CONTEXT: Hepatitis B virus (HBV) and hepatitis C virus (HCV) infections constitute a major global health problem. About 60,000 and 350,000 deaths occur as the results of HBV and HCV infections, respectively. Chronic hepatitis B and C infections are leading causes of cirrhosis and hepatocellular carcinoma (HCC) which are considered as the third cancer-associated cause of deaths worldwide. Iran suffers from the same problem but to a lesser extent as it is considered as a low endemic area for HBV and HCV infections and also as a low incidence area of HCC. This study was conducted to assess and provide a clear picture about epidemiology of HBV and HCV infections in Iran and worldwide, with the consequence on HCC distribution all over the world including Iran, and to analyze current literature regarding the modes of transmission and risk factors of HBV and HCV infections. EVIDENCE ACQUISITION: In this review, we performed electronic and manual searches on available databases such as MEDLINE, PubMed, Ovid, Embase, and the Iranian databases such as IranMedex. We also performed a Google search to find related articles. RESULTS: HBV and HCV infections are the most common risk factors of hepatocellular carcinoma. The epidemiology of HCC usually follows that of HBV and HCV infections. With the introduction of HBV national vaccine in Iran and worldwide, there is a noticeable effect on reduction in HBV prevalence in most countries, and we expect that HCV will replace HBV as a major risk factor of HCC in Iran and worldwide. Alcohol plays a minor role as a risk factor for cirrhosis and HCC in Iran, Asia, and Africa, despite its noticeable role in Europe and the USA. CONCLUSIONS: Vaccination against HBV remains the most effective approach against HBV infection with consequence decrease in HBV-related HCC. There is a need to improve the awareness about epidemiology of HBV and HCV infections, modes of transmission, and their complications, specifically HCC among population.